IDIOPATIC LIVER RUPTURE: AN ITALIAN CASE REPORT - Davide Ferorelli (Euromediterranean Biomedical Journal, 2021)
The liver can be damaged from an impact (such as in a car accident) or from penetrating trauma (such as a stab or gunshot wound). Liver lesions range from relatively small collections of blood (hematomas) to large deep lacerations. Since the liver is supplied with many large blood vessels, the main problem following a liver injury is severe bleeding. Almost all bleeding from a liver injury occurs in the abdominal cavity. Spontaneous rupture of the liver is a rare occurrence. This is often associated with underlying pathological conditions (pregnant women with HELLP syndrome, liver pathologies such as adenoma, hepatic lymphoma, hepatocellular carcinoma HCC, macronodular cirrhosis, hemangioma, metastatic tumors and peliosis hepatis) or following traumatic insults. The authors report a rare case of spontaneous rupture of the liver that occurred in a 72-year-old man without underlying pathologies predisposing this condition, in the absence of evident traumatic lesions in the abdominal area and with a near- negative pathological history of trauma (falls, road accidents, etc.).